Economic Valuation of Marine Tourism in Small Island Using Travel Cost Method (Case Study: Untung Jawa Island, Indonesia) - Firman Zulpikar; Leo Alexander Tambunan; Siti Rahmi Utami; Warsono El Kiyat (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
Marine tourism activities in small islands have an important role in the development of Indonesia maritime sector. This study aimed to estimate the economic value of marine tourism activities in Untung Jawa Island. Individual Travel Cost Method (ITCM) was selected to analyze the level of tourism demand of Untung Jawa. Samples were taken from three different season visits are weekday, weekend, and national holidays. The results showed the factors that have an effect on the level of tourist demand of Untung Jawa Island are travel cost, income, and distance to the location. The potential economic value of marine tourism Untung Jawa Island was IDR 68,505,101,600 with consumer surplus of IDR 397,592 per individual trip. This value is higher than the average of actual visitor expenditure which reached IDR 296,860 per individual trip. Tourism activity has a positive impact on economic conditions of local communities. The results of this study have provided useful information for sustainable management of marine resources.